Interjurisdictional competition and the efficiency of the public sector: The triumph of the market over the state? - Michael Rauscher (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1996)
It has been argued in the literature that, interjurisdictional competition forces the public sector to increase its efficiency and thus helps to tame Leviathan governments. The paper addresses this hypothesis by means of a simple taxcompetition model with a Leviathan state. It is seen that the effects of increased factor mobility on the efficiency of the public sector are ambiguous. A calibration of the model shows that a reduction in public-sector efficiency is possible for parameter constellations which are not unrealistic.
Keywords: F20; H21; H40; H73; 330; Steuerwettbewerb; Public Choice; Öffentlicher Sektor; Wirtschaftliche Effizienz; Faktormobilität; Institutionalismus; Theorie